Beyond second-line therapy in patients with metastatic colorectal cancer: a systematic review. (14th February 2018) - Arnold, D; Prager, G W; Quintela, A; Stein, A; Moreno Vera, S; Mounedji, N; Taieb, J
Abstract: Background: The optimal chemotherapeutic regimen for use beyond the second line for patients with metastatic colorectal cancer (mCRC) remains unclear. Materials and methods: We systematically searched the Cochrane Database of Systematic Reviews, EMBASE and Medline for records published between January 2002 and May 2017, and cancer congress databases for records published between January 2014 and June 2017. Eligible studies evaluated the efficacy, safety and patient-reported outcomes of monotherapies or combination therapies at any dose and number of treatment cycles for use beyond the second line in patients with mCRC. Studies were assessed for design and quality, and a qualitative data synthesis was conducted to understand the impact of treatment on overall survival and other relevant cancer-related outcomes. Results: The search yielded 938 references of which 68 were included for qualitative synthesis. There was limited evidence to support rechallenge with chemotherapy, targeted therapy or both. Compared with placebo, an overall survival benefit for trifluridine/tipiracil (also known as TAS-102) or regorafenib has been shown for patients previously treated with conventional chemotherapy and targeted therapy. There was no evidence to suggest a difference in efficacy between these treatments. Patient choice and quality of life at this stage of treatment should also be considered when choosing an appropriate therapy. Conclusions: These findings support the introduction of an approved agent such as trifluridine/tipiracil or regorafenib beyond the second line before any rechallenge in patients with mCRC who have failed second-line treatment.